Transamidation‐based vitrimers from renewable sources. Issue 25 (25th March 2022) - Pettazzoni, Luca; Leonelli, Francesca; Martinelli, Andrea; Migneco, Luisa Maria; Alfano, Sara; Di Luca, Daniele; Celio, Lorenzo; Di Lisio, Valerio
Abstract: Vitrimers are polymeric materials that behave as thermosets at room temperature but, when heated, they exhibit a plastic flow similar to thermoplastics, enabling their reprocessability. A series of new bio‐based polyamide‐polyamine vitrimers are synthetized starting from tris(2‐aminoethyl)amine and epoxidized methyl oleate, a material that can be easily prepared from renewable resources obtainable both from natural products and waste. The incorporation of free amine groups in the network enables the transamidation exchange reaction with the crosslinking amide functions; this reaction, if appropriately catalyzed, donates a full reprocessability to the material. Boric acid, which is known to be a green, cheap and non‐toxic catalyst for transamidation reactions, is employed in this work. Once that the optimal condition for the transamidation reaction is found, different catalyst loadings are tested and the obtained materials are subjected to thermal and mechanical characterization. The obtained materials possess good thermal stability up to 300°C and a T g value ranging between 7 and 21°C depending on the B(OH)3 content. Furthermore it is possible to observe how the introduction of boric acid in the materials reduces the E a (inferred from stress‐relaxation experiments) of the transamidation reaction from 130 ± 8 KJ mol −1 to a mean value of 63 ± 4 KJ mol −1 . Abstract :